29 Assessing long term transcatheter aortic valve implantation (tavi) function by clincal echocardiography at a single uk tavi centre. (5th June 2017) - Uddin, Akhlaque; To, Ken-win; Woods, Imogen; Kassou, Sofia; Roberts, Elved; Adlam, David; Chin, Derek; Kovac, Jan
Abstract : Background: Recent concerns regarding long term transcatheter aortic valve implantation (TAVI) prosthesis failure have been raised. Studies with long term failure outcomes are limited. Objective: A cross sectional study to assess TAVI prosthesis function after more than 5 years implantation. Method: All successful TAVI procedures at a single high volume centre between January 2007 to December 2012 were included. The most recent clinical transthoracic study assessing for prosthetic function performed by accredited cardiac sonographers and physicians were reviewed. The duration of follow up scan was categorised to early (<12 months), medium term (12 to 48 months) and long term (>48 months). Patient mortality data was recorded. Results: 212 TAVI procedures were successfully implanted with follow up ranging from 4 to 9 years. The characteristics are similar to the first generation TAVI population with predominant use of a femoral approach and a self-expanding device. 4 (1.8%) patients died pre-discharge. 30 day mortality was, 3.3%. 1st, 2nd, 3rd, 4th years mortality were 11.9%, 7.0%, 13.9%, 16.9% respectively. Survival at 5 years was 53.3%. There were fewer patients with follow-up scans beyond 48 months. Cross sectional comparison did not show a change in valve gradient. Mild paravalvular regurgitation was present consistently. There was no evidence of late aortic stenosis or severe AR. Conclusion: The medium to long term 1st generation TAVI valve function is promising, but long term follow up will be difficult due to high mortality in the earlier implantations.